A Simplified Nonsurgical Method for the Correction of Neonatal Deformational Auricular Anomalies. (February 2017) - Chang, Catherine S.; Bartlett, Scott P.
Despite reported success of early nonsurgical splinting of congenital ear deformities, the technique has not been widely utilized due to difficulty with application and positional maintenance of these devices. Delay in treatment can result in unnecessary surgery for the child later in life. In response to this need, we developed a simplified system consisting of Velcro, conformers, and polysiloxane gel that can be applied in 3 steps. Before and after photos after application of the device were graded by a plastic surgeon independent of the study. A total of 33 ear deformities were treated. In all, 92.3% of ears achieved significant improvement and normalization of their ears after therapy. This device allows for a more straightforward and individualized application than current products available. Our hope is that practitioners involved early in the infant's care will utilize this technology resulting in improved outcomes and avoiding unnecessary surgery.